The Influence of Academic Stress and Adversity Intelligence on School Well-Being: The Influence of Academic Stress and Adversity Intelligence on School Well-Being - Diyah Fitriasti Khairunnisa; Nurul Hidayah; Yuzarion (Journal of Family Sciences, 2021)
Learning should provide a pleasant atmosphere for students to fulfill their curiosity. A comfortable atmosphere will bring up student welfare (school well-being). This study aims to determine the influence of academic stress and adversity intelligence on school well-being in Muhammadiyah Al Mujahidin Junior High School students while studying from home during the Covid-19 pandemic. The method researchers use in data collection is a quantitative approach and data collection with a scale or questionnaire and is carried out in June–October 2021. Respondents in this study are junior high school students aged 12-15 years. The number of respondents in this study was 253 students at SMP Muhammadiyah Al Mujahidin. Data collection in this study was conducted using Google Form. The sampling technique used in this research is cluster random sampling. The instrument used is the academic stress scale, adversity intelligence scale, and scale of school well-being. The data analysis technique used is multiple linear regression analysis. Results of addressing a major hypothesis there is a highly significant association of academic stress and adversity intelligence to the well-being of school students of SMP Muhammadiyah AlMujahideen while studying from home to the pandemic covid 19.